Significant Trends in Asia’s Wellness Tourism and Research Agenda: A Systematic Literature Review Analysis - Sangeeta Tripathi; Foued Ben Said (Journal of Tourismology)
The research paper focused on the significant trends in the Wellness market, its demands and motivational factors, and the wellness tourism research agenda and policies that impact the Asian Wellness tourism industry in an Asian context. In a critical systematic literature review, the articles published on wellness topics in 143 Asian documents were selected from the Scopus and Web of Science databases published between 2003 and 2022. The performance analysis revealed that the theme’s production reached an average annual growth rate of 17.67%. The recent trend of wellness tourism in Asian countries is based on wellness retreats that included holistic packages of services such as yoga, meditation, ayurvedic healing, spas, traditional experiences, forest parks, nature sceneries, characteristics food, ancient villages, hot springs, and mental healing. However, the research agenda was usually mixed with health and medical tourism. Health, satisfaction, experiences, and wellness tourism were used the most in the literature. This research paper presents deep insights to help policymakers develop policies which organizes and promotes their country’s wellness tourism. It can be a reference document for further studies in wellness tourism in Asian countries.